ESTIMATION OF CARBON STORAGE AND ECONOMIC VALUE OF CARBON IN THE MANGROVE FOREST ECOSYSTEM OF BENGKALIS DISTRICT, BENGKALIS REGENCY, INDONESIA - Silvi Oktaviona; Syafruddin Nasution; Joko Samiaji (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Mangrove ecosystems play a crucial role in climate change mitigation by absorbing and storing carbon in biomass and sediments. This study aimed to estimate biomass carbon stocks, sediment carbon, CO₂ sequestration, and the economic value of mangrove carbon. The research was conducted in May 2025 in Bengkalis District, Bengkalis Regency. A survey method was employed, utilizing data on mangrove species composition, tree density, and diameter at breast height (DBH). The results identified six mangrove species: Rhizophora apiculata, R. mucronata, Avicennia alba, Sonneratia alba, Xylocarpus granatum, and Excoecaria agallocha. The mangrove ecosystem in Bengkalis District exhibited an average aboveground tree carbon stock of 87.75 t ha⁻¹, root carbon stock of 36.77 t ha⁻¹, sediment carbon stock of 54.03 t ha⁻¹, and CO₂ sequestration of 456.97 t ha⁻¹. The estimated economic value of carbon was IDR 388,342,353 ha⁻¹. These findings indicate that the mangrove ecosystem in Bengkalis District has substantial potential as a carbon sink and storage system, highlighting the importance of sustainable management strategies to support climate change mitigation efforts